2020
DOI: 10.1016/j.heliyon.2020.e03166
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest heat treatments to inhibit Penicillium digitatum growth and maintain quality of Mandarin (Citrus reticulata blanco)

Abstract: Use of fungicides is a common practice as a postharvest treatment to control fruit decay. Nowadays, environment friendly technologies, such as heat treatments, are viable replacements. This study evaluated the effects of postharvest heat treatments (traditional and microwave-assisted) on mandarins intentionally inoculated with Penicillium digitatum. For the studied heat treatments, the target temperature was 50 C, which was held for 2.5 min. After heating, mandarins were cooled and stored at 25 C for 13 days. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
3
7
0
Order By: Relevance
“…Findings of current work showed that the hot water treatment is effective for the prevention of the postharvest weight loss and retention of the fruit quality. Results of present study are in agreement with the ndings of Queb-Gonzalez et al [23] who reported that the postharvest heat treatments prevent the weight loss at mandarin fruits. Hot water treatment was also recommended by several other studies for different citrus species [24,26].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Findings of current work showed that the hot water treatment is effective for the prevention of the postharvest weight loss and retention of the fruit quality. Results of present study are in agreement with the ndings of Queb-Gonzalez et al [23] who reported that the postharvest heat treatments prevent the weight loss at mandarin fruits. Hot water treatment was also recommended by several other studies for different citrus species [24,26].…”
Section: Discussionsupporting
confidence: 94%
“…Previous studies reported that the use of edible coatings [10][11][12] propolis [13], chitosan [14], plants extract or essential oils [15][16][17][18][19] calcium salts [20,21] provides successful control of postharvest fruit decay and improves the storability of fruits. Apart from this, postharvest heat treatment has also reported to provide effective control of postharvest decay and prevent quality loss in storage rooms [22][23][24][25][26]. Previous studies show that both bio-materials and hot water treatment are effective in improving the postharvest storage quality of fruits, but the combination of these studies is very limited.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that the use of edible coatings [10][11][12] propolis [13], chitosan [14], plants extract or essential oils [15][16][17][18][19] calcium salts [20,21] provides successful control of postharvest fruit decay and improves the storability of fruits. Apart from this, postharvest heat treatment has also reported to provide effective control of postharvest decay and prevent quality loss in storage rooms [22][23][24][25][26]. Previous studies show that both bio-materials and hot water treatment are effective in improving the postharvest storage quality of fruits, but the combination of these studies is very limited.…”
Section: Introductionmentioning
confidence: 99%
“…Thermocouple sensors are being used for monitoring temperature within the fruit. Sensors were added below mesocarp and in the center of the fruit to study fruit changes during hot water treatments [58]. Three thermocouples of type J were As well after keeping the fruits for nine and 15 days at ambient storage, 10 prickly pears were cut nearby the sealed surface and in the middle of the fruit to measure TSS changes.…”
Section: Prickly Pear Temperature Measurementsmentioning
confidence: 99%
“…Heat treatment caused important changes in Postharvest Technology -Recent Advances, New Perspectives and Applications epicuticular wax altering microcrack structure. Mandarins were immersed in hydrothermal treatments, maintaining the fruit surface temperature at 50°C for 2.5 min [58]. Once the mandarin peel heats up, thermal energy transfers by conduction to subsequent layers toward the center.…”
Section: Introductionmentioning
confidence: 99%